Women’s views about contraception requirements for biomedical research participation - Sullivan, Kristen A. (PLoS One, 2019)
The scientific and ethical importance of including women of reproductive age in biomedical research is widely acknowledged. Concerns about preventing fetal exposure to research interventions have motivated requirements for contraception among reproductive aged women in biomedical studies–often irrespective of risks and benefits or a woman’s actual potential for pregnancy, raising important questions about when such requirements are appropriate. The perspectives of women themselves on these issues are largely unexplored. We conducted 140 interviews, 70 in the U.S. and 70 in Malawi, with women either living with or at-risk for HIV, exploring their views about the practice of requiring contraception in clinical trials. A majority of women interviewed from both countries indicated overall support for the practice, with seven themes characterizing advantages and disadvantages raised: reproductive control, health effects, prevention of fetal harm, burden on women, deferral to authority, autonomy regarding enrollment and birth control method, and relationship concerns. While women in the US frequently raised prevention of fetal harm as a key advantage, many other positives noted by women in both countries were related to contraception use in general, not specific to a trial context. With regard to disadvantages, U.S. women tended to focus on biomedical risks such as side effects and impact on fertility, whereas Malawian women focused on the social risks of contraception requirements, including violations of trust in marital relations and suspicions of potential infidelity. Given the potential benefits and burdens highlighted, contraception in research should be sensitive to actual fetal risk assessments; directed where justified at optimizing effective pregnancy prevention; responsive to women’s reproductive preferences; and made available as an ancillary benefit even where risk thresholds do not justify requirement–in order to facilitate trials that are both ethical and robustly oriented around the interests and lives of women who will participate in them.